Statin Induced Changes in Rat Pancreatic Tissue: A Histological and Biochemical Perspective - Qamar, Abdullah; Khan, Hammad Gul; Khan, Muhammad Marghoob; Kiani, Muhammad Rizwan Bashir; Kundi, Hina; Mushtaq, Fareeha (Journal of Rawalpindi Medical College, 2024)
Objective: This study aimed to elucidate the effects of simvastatin on pancreatic histomorphology and biochemical profile in a rat model. Method: Forty male Sprague-Dawley rats weighing 250 g were divided into two equal groups: a control group (A) and an experimental group (B) treated with simvastatin 60 mg/kg/day for 12 weeks. At the end of the experiment, the rats were euthanized, and their pancreas was collected for analysis and examined using gold-standard histological parameters including inflammation and fatty infiltration. Biochemical parameters i.e. serum amylase and alkaline phosphatase were also analysed. Statistical Package for the Social Sciences (SPSS) software version 23 was employed for data analysis. Mean ± SD was employed to express quantitative variables. Qualitative variables were expressed as frequencies and percentages. Chi-square tests compared qualitative variables while independent sample t-tests compared quantitative variables between groups, with P < 0.05 defining statistical significance. Results: The administration of Simvastatin resulted in a substantial induction of pancreatic inflammation and fatty infiltration, accompanied by notable alterations in the biochemical profile. Specifically, there was a significant reduction in serum amylase levels and a concomitant increase in serum alkaline phosphatase (ALP) levels, as compared to the control group. Conclusion: This study demonstrates that simvastatin profoundly alters pancreatic histomorphology in rats, resulting in marked inflammation, necrosis, fatty infiltration, and interstitial fibrosis. These novel findings provide unique insights into simvastatin's effects on pancreatic morphology using a robust animal model. Keywords: Simvastatin; Sprague-Dawley rats; pancreatic histomorphology, Amylase, Alkaline phosphatase.